CLINICAL CASE STUDY OF A DIFFICULT-TO-MANAGE PATIENT WITH PSORIATIC ARTHRITIS - O. Malyshenko; N. Evseeva (Clinical Medicine and Pharmacology, 2026)
Psoriatic arthritis is a complex immune–mediated disease in which patients with psoriasis have inflammatory lesions of the musculoskeletal system. A clinical case of curation of a patient with psoriatic arthritis and pustular psoriasis is described. The interaction of the rheumatologist and the dermatologist made it possible to clarify the diagnosis and choose the appropriate treatment tactics for the patient.